Evolution of structural defects in milled Cd0.3Zn0.7 Se powder studied by electron spin spectroscopy - Muh'd, Ibrahim Bagudo; Talib, Zainal Abidin; Sharbaf, Arash Akbari (Elsevier, 2017)
Mechanically induced defect in high energy milled Cd0.3Zn0.7Se nanocrystals was investigated using electron spin resonance (ESR). The broad ESR component with g ∼ 2 was attributed to paramagnetic defects present in the milled powder. The spin density of the center increases linearly from ∼1 × 1020 spins/g to 7 × 1020 spins/g with milling time. The most probable induced centers during mechanical milling were (VZn–Zni), VZn. The best simulations were produced for relative spin concentrations of three paramagnetic defects with ratio 3:6:10 for 5 h and 10 h milled samples.